'Exploiting the Daydreams of Teenagers': Press reports and memories of cinema-going by young people in 1960s Britain. Issue 3 (3rd July 2019) - Glen, Patrick
Abstract : During the 1960s, young people were subject to intense scrutiny. Their lives differed from previous generations and as a consequence, they were portrayed as being at the forefront of social change and representative of Britain's national health. By comparing oral history interviews of those who were young and visited the cinema with media reports, this article evaluates the conversation around 'teenagers.' Newspapers' reports of youth arguably reflected their selection principles and journalistic practices. Oral history narratives, however, complicate press discourse by bringing to the fore a diversity of experiences and understandings: some felt the 'cultural revolution, ' while others felt bored. This demonstrates how studies of reception materials are incomplete and could benefit from being combined with ethnohistorical approaches.